Efektivitas Guru PAI dalam Pengelolaan Kelas di SMK Kabupaten Pidie - Rahmat Rahmat (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
This study aims to determine how effective the performance of PAI teachers in Pidie District Vocational High Schools are and how classroom management is in Pidie District Vocational High Schools. The data collection that the author uses in writing this thesis is a descriptive method, which is a method whose solution is investigated by describing the state of an object and a research at the present time based on the facts that are at the location or as they are and is a field research method, namely by conducting a direct study. the data in the field and also using the library research method, namely by examining books or documents that support the author's language theme. The results of this study indicate that the Effectiveness of PAI Teacher Performance in Vocational High Schools in Pidie Regency both at SMK Negeri 2 and SMK Negeri 3 PAI teachers have carried out their duties well, but not yet fully maximized, only PAI teachers in SMK 2 have been able to interact both to students compared to PAI teachers at SMK 3 Sigli and Class management at Vocational High Schools in Pidie Regency which is carried out at SMK Negeri 2 and SMK Negeri 3 both have shortcomings. PAI teachers at SMK Negeri 2 do not teach with the media in order to facilitate the learning process, while PAI teachers at SMK Negeri 3 are not able to follow the children's language so that children tend to be bored.